Changes to mutual fund risk: Intentional or mean reverting? - Cullen, Grant; Gasbarro, Dominic; Monroe, Gary S.; Zumwalt, J. Kenton (Journal of Banking & Finance, 2012)
An empirical issue is whether a mutual fund’s change in intertemporal risk is intentional or arises from risk mean reversion. Our methodology uses actual fund trades to identify funds that actively change risk. Funds that are statistically identified as trading to change return variance or tracking error variance do not exhibit risk mean reversion. Mostly, funds trade to reduce risk and, in particular, tracking error variance. This is most evident for funds that previously attained a low tracking error variance. We find no evidence of a relation between past performance and intended changes to return variance or tracking error variance.